Composition, carbon fiber precursor, and method for producing carbon fiber precursor

The use of a composition with acrylamide-based copolymer and nitrogen-containing compounds in the carbon fiber precursor composition addresses the viscosity issue, ensuring stable storage and enhanced mechanical properties.

JP2025014511APending Publication Date: 2025-01-30KK TOYOTA CHUO KENKYUSHO +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023117125
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-30

AI Technical Summary

Technical Problem

The challenge of producing carbon fibers is the increase in viscosity due to long-term storage, which affects the storage stability of the composition used in the carbon fiber precursor.

Method used

A composition containing acrylamide-based copolymer with vinyl monomer units having a reactive group of 30 mol% or more, a complex compound with nitrogen atoms, and water, which suppresses the increase in viscosity and enhances storage stability.

Benefits of technology

The composition provides excellent storage stability and enables the production of carbon fiber precursors with improved mechanical properties and processing characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025014511000001
    Figure 2025014511000001
Patent Text Reader

Abstract

To provide a composition or the like with high storage stability.SOLUTION: The present invention provides a composition that comprises an acrylamide-based copolymer containing 30 mol% or more of acrylamide-based monomer units, and vinyl-based monomer units with reactive groups, heterocyclic compounds containing nitrogen atoms, and water, and applications thereof.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to compositions, carbon fiber precursors, and methods for making carbon fiber precursors. [Background technology]

[0002] Conventionally, the main method for producing carbon fibers has been to subject a carbon fiber precursor obtained by spinning polyacrylonitrile to a flame retardant treatment and then to a carbonization treatment. For example, Patent Document 1 discloses a carbon material precursor composition comprising a carbon material precursor made of an acrylamide-based copolymer containing 50 mol % or more of an acrylamide-based monomer unit and 0.5 mol % or more of a vinyl-based monomer unit having a carboxyl group as a copolymerization component, at least one additive component selected from the group consisting of acids and their salts, and a compound having a polyfunctional amino group. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-172800 A Summary of the Invention [Problem to be solved by the invention]

[0004] When a carbon fiber is produced using a composition containing an acrylamide-based copolymer, there are cases where it is required to suppress an increase in viscosity due to long-term storage, that is, to have storage stability.

[0005] An object of one embodiment of the present disclosure is to provide a composition having excellent storage stability. Another problem to be solved by another embodiment of the present disclosure is to provide a carbon fiber precursor using the above composition, and a method for producing a carbon fiber precursor. [Means for solving the problem]

[0006] The present disclosure includes the following aspects. <1> an acrylamide copolymer containing 30 mol % or more of an acrylamide monomer unit and a vinyl monomer unit having a reactive group; a heterocyclic compound containing a nitrogen atom; and water. <2> The composition of claim 1, further comprising a compound having a multifunctional amino group. <3> The vinyl monomer unit having a reactive group is an unsaturated carboxylic acid unit. <1> or <2> The composition described in <4> The viscosity of a composition containing 50% by mass of an acrylamide-based copolymer is defined as viscosity A, and the viscosity of a composition containing 50% by mass of an acrylamide-based copolymer after storage at 70° C. for 24 hours is defined as viscosity B. Viscosity B is within twice the viscosity of viscosity A and is 100 Pa s or less. <1> ~ <3> 13. The composition according to any one of claims 1 to 12. <5> an acrylamide copolymer containing 30 mol % or more of an acrylamide monomer unit and a vinyl monomer unit having a reactive group; A carbon fiber precursor comprising: <6> Further comprising a compound having a multifunctional amino group, <5> Carbon fiber precursor. <7> The vinyl monomer unit having a reactive group is an unsaturated carboxylic acid unit. <5> or <6> The carbon fiber precursor according to claim 1. <8> A method for producing a carbon fiber precursor, comprising a step of spinning a composition containing an acrylamide copolymer containing 30 mol % or more of acrylamide monomer units and vinyl monomer units having a reactive group, a heterocyclic compound containing a nitrogen atom, and water. <9> The composition further comprises a compound having a multifunctional amino group. <8> A method for producing carbon fiber precursors. <10> The vinyl monomer unit having a reactive group is an unsaturated carboxylic acid unit. <8> or <9> A method for producing carbon fiber precursors. Effect of the Invention

[0007] According to one embodiment of the present disclosure, a composition having excellent storage stability is provided. According to another embodiment of the present disclosure, there is provided a carbon fiber precursor using the above composition, and a method for producing a carbon fiber precursor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0009] In the present disclosure, each component may contain multiple types of corresponding substances. When multiple types of substances corresponding to each component are present in the carbon fiber precursor, the content or amount of each component means the total content or amount of the multiple types of substances present in the carbon fiber precursor, unless otherwise specified.

[0010] In the present disclosure, the term "carbon fiber precursor" refers to a fiber that can be subjected to a carbonization treatment, or a flame retardant treatment and a carbonization treatment to obtain a carbon fiber.

[0011] <Composition> The composition of the present disclosure contains an acrylamide-based copolymer containing 30 mol % or more of an acrylamide-based monomer unit and a vinyl-based monomer unit having a reactive group, a heterocyclic compound containing a nitrogen atom, and water.

[0012] The composition of the present disclosure is inhibited from increasing in viscosity due to long-term storage, and has excellent storage stability.

[0013] The reason why the above effect is achieved is presumed to be as follows, but is not limited to this. The composition of the present disclosure includes a heterocyclic compound containing a nitrogen atom. The nitrogen atom of the heterocyclic compound containing a nitrogen atom is coordinated to the reactive group of the vinyl monomer unit having a reactive group contained in the acrylamide copolymer, and it is considered that the gelation of the acrylamide copolymer is suppressed and the storage stability is excellent. In addition, when other components are contained, the reaction between the acrylamide copolymer and other components is suppressed, and the storage stability is excellent.

[0014] Each component contained in the composition of the present disclosure will be described below.

[0015] (Acrylamide copolymer) The acrylamide copolymer contains 30 mol % or more of acrylamide monomer units. That is, the content of acrylamide monomer units in the acrylamide copolymer is 30 mol % or more. The content is preferably 40 mol % or more, and more preferably 50 mol % or more.

[0016] In the present disclosure, an acrylamide-based monomer unit means a structural unit derived from an acrylamide-based monomer.

[0017] When the content of the acrylamide monomer unit is 30 mol % or more, the solubility of the acrylamide copolymer in water can be improved.

[0018] In addition, the upper limit of the content of acrylamide-based monomer units is not particularly limited, but from the viewpoint of shape stability in the carbon fiber precursor, it is preferably 99 mol % or less, more preferably 90 mol % or less, and even more preferably 85 mol % or less.

[0019] Examples of acrylamide monomers include acrylamide, ethacrylamide, crotonamide, itaconic acid diamide, cinnamic acid amide, maleic acid diamide, N-alkyl acrylamides such as N-methyl acrylamide, N-ethyl acrylamide, Nn-propyl acrylamide, N-isopropyl acrylamide, Nn-butyl acrylamide, and N-tert-butyl acrylamide, N-cycloalkyl acrylamides such as N-cyclohexyl acrylamide, dialkyl acrylamides such as N,N'-dimethyl acrylamide, dialkyl amino alkyl acrylamides such as dimethyl amino ethyl acrylamide and dimethyl amino propyl acrylamide, hydroxy alkyl acrylamides such as N-(hydroxy methyl) acrylamide and N-(hydroxy ethyl) acrylamide, N-aryl acrylamides such as N-phenyl acrylamide, diacetone acrylamide, and N,N'-methylene bisacrylamide, etc. N-alkylenebisacrylamides; methacrylamide; N-alkyl methacrylamides such as N-methyl methacrylamide, N-ethyl methacrylamide, Nn-propyl methacrylamide, N-isopropyl methacrylamide, N-n-butyl methacrylamide, and N-tert-butyl methacrylamide; N-cycloalkyl methacrylamides such as N-cyclohexyl methacrylamide; dialkyl methacrylamides such as N,N-dimethyl methacrylamide; dialkylaminoalkyl methacrylamides such as dimethylaminoethyl methacrylamide and dimethylaminopropyl methacrylamide; hydroxyalkyl methacrylamides such as N-(hydroxymethyl) methacrylamide and N-(hydroxyethyl) methacrylamide; N-aryl methacrylamides such as N-phenyl methacrylamide; diacetone methacrylamide; and N,N'-alkylene bismethacrylamides such as N,N'-methylene bismethacrylamide.

[0020] Furthermore, from the viewpoint of the solubility of the acrylamide-based copolymer in water, among the above-mentioned acrylamide-based monomers, acrylamide, N-alkylacrylamide, dialkylacrylamide, methacrylamide, N-alkylmethacrylamide or dialkylmethacrylamide is preferred, and acrylamide is more preferred.

[0021] The acrylamide-based monomer unit contained in the acrylamide-based copolymer may be of only one type, or of two or more types.

[0022] The acrylamide copolymer contains a vinyl monomer unit having a reactive group. In the present disclosure, the vinyl monomer unit having a reactive group means a structural unit derived from a vinyl monomer having a reactive group.

[0023] The reactive group in the vinyl monomer having a reactive group is preferably a reactive group capable of reacting with an amino group, and more preferably at least one selected from the group consisting of a carboxy group, an acid anhydride group, an ester group, and an epoxy group.

[0024] Specifically, the vinyl monomer unit having a reactive group is preferably at least one selected from the group consisting of an unsaturated carboxylic acid unit, an unsaturated carboxylic anhydride unit, an unsaturated carboxylic ester unit, and an epoxy group-containing vinyl monomer unit. The unsaturated carboxylic acids include acrylic acid, methacrylic acid, maleic acid, fumaric acid, and italic acid. Examples of the acid include citraconic acid, mesaconic acid, crotonic acid, and isocrotonic acid.

[0025] The unsaturated carboxylic acid may form a salt. Examples of the salt of the unsaturated carboxylic acid include a metal salt (e.g., a sodium salt, a potassium salt, etc.), an ammonium salt, and an amine salt of the unsaturated carboxylic acid.

[0026] Examples of the unsaturated carboxylic acid anhydride include maleic anhydride and itaconic anhydride.

[0027] Examples of unsaturated carboxylate esters include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-propyl acrylate, n-propyl methacrylate, n-butyl acrylate, n-butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, sec-butyl acrylate, sec-butyl methacrylate, t-butyl acrylate, t-butyl methacrylate, n-hexyl acrylate, n-hexyl methacrylate, lauryl acrylate, lauryl methacrylate, dodecyl acrylate, dodecyl methacrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, cyclohexyl acrylate, cyclohexyl methacrylate, stearyl acrylate, stearyl methacrylate, octadecyl acrylate, octadecyl methacrylate, phenyl acrylate, phenyl methacrylate, benzyl acrylate, benzyl methacrylate, allyl acrylate, methacryloyl acrylate, methyl acrylate, methyl meth ... Examples of the acrylate include allyl acrylate, trifluoroethyl acrylate, trifluoroethyl methacrylate, chloromethyl acrylate, chloromethyl methacrylate, 2-chloroethyl acrylate, 2-chloroethyl methacrylate, 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 2,3,4,5,6-pentahydroxyhexyl acrylate, 2,3,4,5,6-pentahydroxyhexyl methacrylate, ethylhexyl acrylate, ethylhexyl methacrylate, 2,3,4,5-tetrahydroxypentyl acrylate, 2,3,4,5-tetrahydroxypentyl methacrylate, aminoethyl acrylate, propylaminoethyl acrylate, dimethylaminoethyl methacrylate, ethylaminopropyl methacrylate, phenylaminoethyl methacrylate, and cyclohexylaminoethyl methacrylate.

[0028] Examples of the epoxy group-containing vinyl monomer include glycidyl acrylate, glycidyl methacrylate, glycidyl itaconate, allyl glycidyl ether, styrene-p-glycidyl ether, and p-glycidyl styrene.

[0029] The vinyl monomer unit having a reactive group contained in the acrylamide copolymer may be of only one type or of two or more types.

[0030] In the acrylamide copolymer, the content of the vinyl monomer unit having a reactive group is preferably 0.1 mol % to 40 mol %, and more preferably 1 mol % to 10 mol %.

[0031] The acrylamide copolymer may contain a constituent unit derived from a polymerizable monomer other than the acrylamide monomer unit and the vinyl monomer unit having a reactive group.

[0032] Examples of other polymerizable monomers include vinyl cyanide monomers, olefin monomers, vinyl carboxylate monomers, aromatic vinyl monomers, vinyl halide monomers, vinyl alcohol monomers, and vinyl sulfonate monomers.

[0033] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, 2-hydroxyethyl acrylonitrile, chloroacrylonitrile, chloromethyl acrylonitrile, ethoxyacrylonitrile, and vinylidene cyanide.

[0034] Examples of the olefin monomer include ethylene, propylene, isopropylene, and butadiene. Examples of the vinyl carboxylate monomer include vinyl acetate, propenyl acetate, isopropenyl acetate, and vinyl benzoate.

[0035] Examples of the aromatic vinyl monomer include styrene, α-methylstyrene, vinyltoluene, o-ethylstyrene, pt-butylstyrene, p-methylstyrene, chlorostyrene, and bromostyrene.

[0036] Examples of the vinyl halide monomer include vinyl chloride.

[0037] The vinyl alcohol monomer includes vinyl alcohol.

[0038] Examples of the sulfonic acid vinyl monomer include vinyl sulfonic acid, vinylbenzenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and salts thereof.

[0039] Among these, from the viewpoints of spinnability, fusion suppression, carbonization yield and shape stability of the acrylamide copolymer, vinyl cyanide monomers are preferred, and acrylonitrile is more preferred.

[0040] The acrylamide copolymer may contain only one type of other polymerizable monomer unit, or may contain two or more types.

[0041] The content of other polymerizable monomer units in the acrylamide copolymer is preferably from 1 mol % to 50 mol %, and more preferably from 10 mol % to 40 mol %.

[0042] From the viewpoints of solubility in water, spinnability, fusion suppression, carbonization yield and shape stability, the acrylamide-based copolymer is particularly preferably a copolymer of an acrylamide-based monomer, a vinyl cyanide-based monomer and an unsaturated carboxylic acid, and is most preferably a copolymer of acrylamide, acrylonitrile and acrylic acid.

[0043] The weight average molecular weight of the acrylamide copolymer is not particularly limited and is usually 5 million or less. From the viewpoint of molding processability of the carbon fiber precursor, however, it is preferably 2 million or less, more preferably 1 million or less, even more preferably 500,000 or less, particularly preferably 200,000 or less, even more preferably 130,000 or less, and most preferably 100,000 or less.

[0044] In addition, the lower limit of the weight average molecular weight of the acrylamide-based copolymer is not particularly limited, but is usually 10,000 or more. From the viewpoint of the strength of the carbon fiber precursor and the carbon fiber, it is preferably 20,000 or more, more preferably 30,000 or more, and particularly preferably 40,000 or more.

[0045] In the present disclosure, the weight average molecular weight is measured by gel permeation chromatography under the following conditions. The measurement device may be HLC-8220GPC manufactured by Tosoh Corporation or a device equivalent thereto. (Measurement conditions) Column: TSKgel GMPWXL x 2 + TSKgel G2500PWXL x 1 Eluent: 100 mM sodium nitrate aqueous solution / acetonitrile (=80 / 20 (volume ratio)) ·Eluent flow rate: 1.0ml / min Column temperature: 40℃ Molecular weight standards: Standard polyethylene oxide / Standard polyethylene glycol Detector: Refractive index detector

[0046] (Heterocyclic compounds containing nitrogen atoms) The compositions of the present disclosure include nitrogen-containing heterocyclic compounds. Examples of the nitrogen-containing heterocyclic compounds include three-membered ring heterocyclic compounds such as aziridine, diaziridine, azirine, diazirine, and diazylene; four-membered ring heterocyclic compounds such as azetidine, diazetidine, triazetidine, azeto, diazeto, and triazeto; five-membered ring heterocyclic compounds such as pyrrolidine, pyrazolidine, imidazolidine, triazolidine, tetrazolidine, pyrroline, pyrazoline, imidazoline, triazoline, tetrizoline, pyrrole, pyrazole, imidazole, triazole, and tetrazole; piperidine, piperideine, piperazine, triazinane, tetrazinane, pentazinane, pyridine, pyridazine, pyrimidine, pyrazine, and triazine. heterocyclic compounds having a six-membered ring such as tetrazine and pentazine; heterocyclic compounds having a seven-membered ring such as azepane, diazepane, triazepane, tetrazepane, azepine, diazepine and triazepine; azocane, azonane, azecane, azocine, azonine and azecine; indole compounds such as indole, indolenine, indoline, isoindole, isoindolenine, isoindoline, indolizine, purine and indolizidine; quinoline compounds such as quinoline, isoquinoline, quinolizidine, quinoxaline, cinnoline, quinazoline, phthalazine and naphthyridine; and tricyclic compounds such as carbazole, phenanthroline, acridine, naphthazine and phenazine.

[0047] The nitrogen-containing heterocyclic compound may be a pyrrolizidine, quinuclidine, diazabicyclooctane, hexamine, diazabicyclononene, diazabicycloundecene, morphan, benzazocine, azepindo, morphinan, hasbanan, porphyrin, chlorin, corrole, norcorrole, corrin, subporphyrin, phthalocyanine, naphthalocyanine, or anthracocyanine.

[0048] The nitrogen-containing heterocyclic compound may be a derivative of the above-mentioned compound or a salt of the above-mentioned compound. The salt may be an organic salt or an inorganic salt.

[0049] Among them, the nitrogen-containing heterocyclic compound is preferably imidazole or an imidazole derivative.

[0050] Examples of imidazole derivatives include alkylimidazole compounds such as 1-decylimidazole, 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 2-ethyl-4-methylimidazole, 2-undecyl-4-methylimidazole, 4-methylimidazole, 4-octylimidazole, and 2-cyclohexylimidazole; alkylimidazole compounds such as 2-phenylimidazole and 2-phenyl-4-methylimidazole; 1-Phenylimidazole, 2-Phenylimidazole, 2-Toluylimidazole, 2-(4-chlorophenyl)imidazole, 2-Phenyl-4-methylimidazole, 2-Phenyl-1-benzylimidazole, 2-Phenyl-4-benzylimidazole, 2,4-Diphenylimidazole, 2,4-Diphenyl-5-methylimidazole, 2-Phenyl-4-(3,4-dichlorophenyl)imidazole, 2-Phenyl-4-(2,4-dichlorophenyl)-5-methylimidazole, 2-(2,4-dichlorophenyl)-4-phenyl-5-methylimidazole, 4-Phenylimidazole, 2-Nonyl-4-phenylimidazole, 4-Phenyl-5-decylimidazole, 2-Phenyl-4-methyl-5-benzylimidazole aryl imidazole compounds such as imidazole, 2-(1-naphthyl)imidazole, 2(2-naphthyl)-4-(4-chlorophenyl)-5-methylimidazole, 2-phenyl-4-(2-naphthyl)imidazole, 2,4,5-triphenylimidazole, 2-(2,4-dichlorophenyl)-4,5-diphenylimidazole, 2-(1-naphthyl)-4,5-diphenylimidazole, and 2-(4-pyridyl)-4,5-diphenylimidazole; aralkylimidazole compounds such as 1-benzylimidazole, 1-(4-chlorophenyl)methyl-2-methylimidazole, 2-benzylimidazole, 2-benzyl-4-methylimidazole, 2-(2-phenylethyl)imidazole, 2-(5-phenylpentyl)imidazole, 2-methyl-4,5-dibenzylimidazole, 1-(2,4-dichlorophenyl)methyl-2-benzylimidazole, and 2-(1-naphthyl)methyl-4-methylimidazole; 1-Dodecyl-2-methylbenzimidazole, 2-Propylbenzimidazole, 2-Pentylbenzimidazole, 2-Octylbenzimidazole, 2-Nonylbenzimidazole, 2-Heptadecylbenzimidazole, 2-Hexyl-5-methylbenzimidazole, 2-Pentyl-5,6-dichlorobenzimidazole, 2-(1-Ethylpentyl)benzimidazole, 2-(2,4,4-Trimethylenediaminetetraacetate) alkylbenzimidazole compounds such as 2-(5-phenylpentyl)benzimidazole, 2-cyclohexylbenzimidazole, 2-(5-cyclohexylpentyl)benzimidazole, 2-phenoxymethylbenzimidazole, 2-(2-aminoethyl)benzimidazole, 2,2'-ethylenedibenzimidazole, 2-(mercaptomethyl)benzimidazole, and 2-pentylmercaptobenzimidazole; Arylbenzimidazole compounds such as 1-phenylbenzimidazole, 2-phenylbenzimidazole, 2-(4-chlorophenyl)benzimidazole, 1-benzyl-2-phenylbenzimidazole, 2-orthotolyl-5,6-dimethylbenzimidazole, 2-(1-naphthyl)-5-chlorobenzimidazole, 5-phenylbenzimidazole, and 2-(2-pyridyl)benzimidazole; 1-Benzylbenzimidazole, 2-benzylbenzimidazole, 2-(4-chlorophenyl)methylbenzimidazole, 2-(4-bromophenyl)methylbenzimidazole, 2-(2,4-dichlorophenyl)methylbenzimidazole, 2-(3,4-dichlorophenyl)methylbenzimidazole, 2-para-tolylmethyl-5,6-dichlorobenzimidazole, 1-allyl-2-(4-chlorophenyl )methylbenzimidazole, 2-(2-phenylethyl)benzimidazole, 2-(3-phenylpropyl)-5-methylbenzimidazole, 2-(1-naphthyl)methylbenzimidazole, 2-(2-phenylvinyl)benzimidazole, 2-(benzylmercapto)benzimidazole, 2-(2-benzylmercaptoethyl)benzimidazole and other aralkylbenzimidazole compounds.

[0051] The content of the nitrogen atom-containing heterocyclic compound is preferably 0.01 to 20 parts by mass, more preferably 0.05 to 10 parts by mass, even more preferably 0.1 to 5 parts by mass, particularly preferably 0.15 to 2 parts by mass, and most preferably 0.2 to 1 part by mass, relative to 100 parts by mass of the acrylamide-based copolymer.

[0052] (water) The compositions of the present disclosure include water.

[0053] The water content is preferably 1 to 4000 parts by mass, more preferably 3 to 2000 parts by mass, even more preferably 10 to 1000 parts by mass, particularly preferably 20 to 900 parts by mass, and particularly preferably 30 to 800 parts by mass, relative to 100 parts by mass of the acrylamide copolymer.

[0054] The composition of the present disclosure may contain components other than the acrylamide-based copolymer, the heterocyclic compound containing a nitrogen atom, and water.

[0055] From the viewpoint of suppressing fusion or aggregation of carbon fiber precursors caused by softening of the acrylamide-based copolymer at high temperatures (e.g., 200°C or higher) during the flame retardant treatment and improving shape retention, it is preferable that the composition of the present disclosure further contains a compound having a multifunctional amino group (hereinafter also referred to as a "multifunctional amino group-containing compound").

[0056] Examples of polyfunctional amino group-containing compounds include aromatic diamines such as phenylenediamine and diaminonaphthalene; aliphatic diamines such as hexamethylenediamine and diaminooctane; alicyclic diamines such as diaminocyclohexane; dihydrazide compounds such as adipic acid dihydrazide, sebacic acid dihydrazide, dodecanediohydrazide, isophthalic acid dihydrazide, and salicylic acid dihydrazide; and dicyandiamide.

[0057] The polyfunctional amino group-containing compound that may be contained in the composition of the present disclosure may be of only one type, or may be of two or more types.

[0058] When the composition of the present disclosure contains a polyfunctional amino group-containing compound, the content of the polyfunctional amino group-containing compound is preferably 0.01 parts by mass to 20 parts by mass, and more preferably 0.05 parts by mass to 10 parts by mass, relative to 100 parts by mass of the acrylamide-based copolymer.

[0059] When the composition contains a polyfunctional amino group-containing compound, the reaction between the polyfunctional amino group-containing compound and the acrylamide copolymer tends to increase the viscosity of the composition and cause gelation. However, the composition of the present disclosure contains a heterocyclic compound containing a nitrogen atom, so that the reaction between the polyfunctional amino group-containing compound and the acrylamide copolymer is suppressed, and the composition has excellent storage stability.

[0060] The composition of the present disclosure preferably further contains at least one selected from the group consisting of acids and salts thereof.

[0061] Examples of the acid include inorganic acids such as phosphoric acid, polyphosphoric acid, boric acid, sulfuric acid, nitric acid, and carbonic acid, and organic acids such as oxalic acid, citric acid, and sulfonic acid. Examples of the salts of such acids include metal salts (e.g., sodium salts and potassium salts), ammonium salts, amine salts, guanidine salts, urea salts, melamine salts, and imidazole salts, with ammonium salts and amine salts being preferred, and ammonium salts being more preferred. From the viewpoint of further improving the carbonization yield of the carbon material precursor, the at least one selected from the group consisting of acids and salts thereof is preferably phosphoric acid, polyphosphoric acid, boric acid, sulfuric acid, or an ammonium salt thereof, more preferably phosphoric acid, polyphosphoric acid, boric acid, or an ammonium salt thereof, and particularly preferably phosphoric acid, polyphosphoric acid, or an ammonium salt thereof.

[0062] When the composition of the present disclosure contains at least one selected from the group consisting of acids and salts thereof, the content thereof is preferably 0.1 to 100 parts by mass, more preferably 0.2 to 50 parts by mass, even more preferably 0.5 to 30 parts by mass, and particularly preferably 1 to 20 parts by mass, relative to 100 parts by mass of the acrylamide-based copolymer.

[0063] In the composition of the present disclosure, the acrylamide-based copolymer may be dissolved in water or may be dispersed in water, i.e., the composition of the present disclosure may be an aqueous solution or an aqueous dispersion.

[0064] The composition of the present disclosure preferably has a viscosity at 70° C. of 1 Pa·s to 200 Pa·s, and more preferably 10 Pa·s to 100 Pa·s.

[0065] When the viscosity of a composition containing 50% by mass of an acrylamide-based copolymer is defined as viscosity A and the viscosity of the composition containing 50% by mass of an acrylamide-based copolymer after storage at 70°C for 24 hours is defined as viscosity B, it is preferable that viscosity B is within twice the viscosity A and is 200 Pa s or less, and it is more preferable that viscosity B is within twice the viscosity A and is 100 Pa s or less.

[0066] The viscosities A and B are values ​​measured using a Brookfield viscometer for a composition adjusted to 70° C. As the viscometer, for example, a viscometer “TVC-10” manufactured by Toyo Sangyo Co., Ltd. is used.

[0067] <Carbon fiber precursor> The carbon fiber precursor of the present disclosure contains an acrylamide-based copolymer containing 30 mol % or more of an acrylamide-based monomer unit and a vinyl-based monomer unit having a reactive group, and a heterocyclic compound containing a nitrogen atom.

[0068] The preferred embodiments of the acrylamide copolymer and the nitrogen atom-containing heterocyclic compound are as described above. The carbon fiber precursor of the present disclosure may further contain other components other than the acrylamide copolymer and the heterocyclic compound containing a nitrogen atom. The carbon material precursor of the present disclosure may further contain additive components such as other polymers, organic solvents, surfactants, crosslinking agents, flame retardant accelerators (e.g., acids, their salts, etc.), chlorides such as sodium chloride and zinc chloride; hydroxides such as sodium hydroxide; glass fibers, carbon black, carbon nanotubes; various fillers such as graphene; dispersants, smoothing agents, moisture absorbents, viscosity modifiers, plasticizers, release agents, spreading agents, antioxidants, antibacterial agents, preservatives, rust inhibitors, and pH adjusters. The content of the additive components can be appropriately adjusted.

[0069] The carbon fiber precursor of the present disclosure includes a heterocyclic compound containing a nitrogen atom. The nitrogen atom of the heterocyclic compound containing a nitrogen atom is coordinated to the reactive group of the vinyl monomer unit having a reactive group contained in the acrylamide copolymer, thereby improving the mechanical properties (particularly, tensile strength).

[0070] The carbon fiber precursor may be a single fiber or a fiber bundle.

[0071] When the carbon fiber precursor is a fiber bundle, the number of filaments per bundle is not particularly limited, but from the viewpoint of the productivity and mechanical properties of the flame-resistant fiber and carbon fiber, it is preferably 50 to 360,000, more preferably 100 to 144,000, even more preferably 500 to 36,000, and particularly preferably 1,000 to 24,000. Furthermore, by setting the number of filaments per bundle to 360,000 or less, the occurrence of uneven firing during the flame-resistant treatment can be suppressed.

[0072] The single fiber fineness of the carbon fiber precursor is not particularly limited, but is preferably 1×10 -8 Preferably, the density is 1×10 -6 tex / line to 60tex / line is more preferable, and 1×10 -3 It is more preferable that the thickness is 1×10 -2 It is even more preferable that the thickness is between tex / thread and 10 tex / thread, 2×10 -2 It is particularly preferable that the thickness is 3×10 -2 tex / book~3×10 -1 tex / book is most preferred. The fineness of the carbon fiber precursor is 1×10 -8 By making it tex / string or more, the occurrence of yarn breakage can be suppressed, which tends to improve the ease of winding the carbon fiber precursor and the stability of the flame retardant treatment. By setting the single fiber fineness of the carbon fiber precursor to 100 tex / fiber or less, the difference between the structure near the surface and the structure near the center of the carbon fiber obtained by the flame retardant treatment can be reduced, and the tensile strength and tensile modulus of the carbon fiber can be improved.

[0073] In the present disclosure, the measurement of the single fiber fineness (tex / fiber) is performed by bundling 100 carbon fiber precursors to prepare a fiber bundle, measuring the mass of this fiber bundle, and calculating the single fiber fineness according to the following formula. Single fiber fineness (tex) = fiber bundle mass (g) / fiber length (m) x 1000 / 100 (pieces)

[0074] The average fiber diameter of the carbon fiber precursor is not particularly limited, but is preferably 3 nm to 300 μm, more preferably 30 nm to 250 μm, even more preferably 1 μm to 200 μm, particularly preferably 3 μm to 100 μm, even more preferably 4 μm to 40 μm, most preferably 5 μm to 30 μm, and may be 6 μm to 20 μm. By making the average fiber diameter of the carbon fiber precursor 3 nm or more, the stability of the flame retardant treatment tends to be improved. In addition, by making the average fiber diameter of the carbon fiber precursor 3 nm or more, the occurrence of yarn breakage can be suppressed, and thus the ease of winding the carbon fiber precursor and the stability of the flame retardant treatment tend to be improved. By setting the average fiber diameter of the carbon fiber precursor to 300 μm or less, the difference between the structure near the surface layer and the structure near the center of the carbon fiber obtained by the flame retardant treatment can be reduced, and the tensile strength and tensile modulus of the carbon fiber tend to be improved.

[0075] In the present disclosure, the average fiber diameter is determined by bundling 100 carbon fiber precursors to prepare a fiber bundle, measuring the density of the fiber bundle using a dry automatic density meter, and calculating the average fiber diameter of the single fibers constituting the fiber bundle using the following formula. As the dry automatic density meter, an Accupyk II 1340 manufactured by Micromeritics or an equivalent device can be used. D = {(Dt × 4 × 1000) / (ρ × π × n)} 1 / 2 [During the ceremony, D represents the average fiber diameter (μm) of the single fibers constituting the fiber bundle, Dt represents the fiber bundle fineness (tex), ρ is the density of the fiber bundle (g / cm 3 ), n represents the number of single fibers that make up the fiber bundle. In addition, π is 3.14.

[0076] The carbon fiber precursor of the present disclosure may have a surface coated with a conventionally known oil agent. By applying an oil agent to the surface of the carbon fiber precursor, the bundling property and handling of the fibers can be improved, and fusion of the single fibers to each other can be prevented. Furthermore, by crosslinking the oil together with the acrylamide copolymer, fusion of the single fibers to each other can be more effectively prevented. The oil is not particularly limited, but from the viewpoint of suppressing fusion between single fibers, a silicone-based oil is preferably used. Furthermore, the oil is preferably an oil having a functional group that crosslinks upon irradiation with actinic rays and / or heat, more preferably a silicone-based oil having a functional group, and particularly preferably a silicone-based oil having a functional group that crosslinks upon irradiation with actinic rays.

[0077] <Method of manufacturing carbon fiber precursor> The method for producing a carbon fiber precursor of the present disclosure includes a step of spinning a composition including an acrylamide-based copolymer containing 30 mol % or more of an acrylamide-based monomer unit and a vinyl-based monomer unit having a reactive group, a heterocyclic compound containing a nitrogen atom, and water.

[0078] A preferred embodiment of the composition used in the method for producing a carbon fiber precursor of the present disclosure is the same as the preferred embodiment of the composition of the present disclosure.

[0079] The spinning method is not particularly limited, and examples thereof include dry spinning, dry-wet spinning, wet spinning, melt spinning, and electrospinning. Among them, dry spinning using at least one of an aqueous solvent (for example, water, alcohol, and a mixed solvent thereof) and an aqueous mixed solvent (a mixed solvent of an aqueous solvent and an organic solvent (dimethyl sulfoxide, dimethylformaldehyde, tetrahydrofuran, etc.)) is preferred, which makes it possible to safely produce carbon fibers at low cost. The content of the organic solvent in the aqueous mixed solvent is not particularly limited as long as the amount of an acrylamide-based copolymer that is insoluble or poorly soluble in an aqueous solvent is dissolved by mixing the organic solvent. Among such acrylamide-based copolymers, an acrylamide-based copolymer that is soluble in an aqueous solvent is preferred, and an acrylamide-based copolymer that is soluble in water (water-soluble) is more preferred, from the viewpoint of making it possible to safely produce carbon fiber precursors and carbon fibers at lower cost.

[0080] The synthesis of the acrylamide copolymer can be carried out by utilizing known polymerization reactions such as radical polymerization, cationic polymerization, anionic polymerization, living radical polymerization, etc. Among the above polymerization reactions, radical polymerization is preferred from the viewpoint of reducing synthesis costs. The synthesis of the acrylamide copolymer can be carried out by utilizing a polymerization method such as solution polymerization, suspension polymerization, precipitation polymerization, dispersion polymerization, or emulsion polymerization (for example, inverse phase emulsion polymerization). Furthermore, when synthesizing an acrylamide-based copolymer by solution polymerization, it is preferable to use a solvent in which the raw material monomers and the resulting acrylamide-based copolymer are soluble. From the viewpoint of low-cost and safe synthesis, it is more preferable to use an aqueous solvent or an aqueous mixed solvent, and even more preferable to use an aqueous solvent. The aqueous solvent may be water, alcohol, a mixture of these, or the like, with water being particularly preferred. The aqueous mixed solvent means a mixed solvent of the above aqueous solvent and an organic solvent, and examples of the organic solvent include tetrahydrofuran, dimethylsulfoxide, and dimethylformaldehyde.

[0081] In the synthesis of the acrylamide copolymer by radical polymerization, it is preferable to use a polymerization initiator. As the polymerization initiator, a conventionally known radical polymerization initiator such as azobisisobutyronitrile, benzoyl peroxide, 4,4'-azobis(4-cyanovaleric acid), ammonium persulfate, potassium persulfate, etc. can be used. When an aqueous solvent or an aqueous mixed solvent is used as the solvent, a radical polymerization initiator soluble in the aqueous solvent or the aqueous mixed solvent, such as 4,4'-azobis(4-cyanovaleric acid), ammonium persulfate, or potassium persulfate, is preferred. From the viewpoint of controlling the molecular weight of the acrylamide-based copolymer and improving the spinnability of the acrylamide-based copolymer, it is preferable to use at least one of a polymerization accelerator and a molecular weight regulator in place of or together with the polymerization initiator, and it is more preferable to use a polymerization initiator and a polymerization accelerator in combination. The polymerization accelerator may, for example, be tetramethylethylenediamine. The molecular weight regulator may, for example, be an alkyl mercaptan compound such as n-dodecyl mercaptan. It is particularly preferable to use ammonium persulfate as a polymerization initiator in combination with tetramethylethylenediamine as a polymerization promoter.

[0082] The temperature of the polymerization reaction is not particularly limited, but from the viewpoint of improving the spinnability of the acrylamide copolymer, it is preferably 35°C or higher, more preferably 40°C or higher, even more preferably 50°C or higher, particularly preferably 70°C or higher, and most preferably 75°C or higher.

[0083] The carbon fiber precursor can be subjected to a flame-retardant treatment to produce a flame-retardant fiber. The flame-retardant treatment refers to subjecting the carbon fiber precursor to a heat treatment in an oxidizing atmosphere.

[0084] In the flame-resistant treatment, the acrylamide copolymer and the nitrogen-containing heterocyclic compound are dissociated, improving the shape retention of the flame-resistant fiber.

[0085] The flame retardant treatment is not particularly limited, but is preferably carried out at a temperature in the range of 150°C to 500°C, more preferably at a temperature in the range of 200°C to 450°C, and even more preferably at a temperature in the range of 250°C to 420°C. The above temperature includes not only the maximum temperature during the flame-resistant treatment (flame-resistant treatment temperature) described below, but also the temperature during the temperature rise process up to the flame-resistant treatment temperature.

[0086] The maximum temperature during the flame retardant treatment (flame retardant treatment temperature) is preferably 250°C to 500°C, more preferably 280°C to 450°C, even more preferably 290°C to 420°C, even more preferably 300°C to 400°C, particularly preferably 305°C to 390°C, and most preferably 310°C to 380°C. By setting the flame-retardant treatment temperature to 250° C. or higher, the heat resistance and carbonization yield of the flame-retardant fiber tend to be improved. Furthermore, by setting the flame-proofing treatment temperature to 500° C. or less, production costs tend to be reduced.

[0087] In the flame-retardant treatment of the carbon fiber precursor, it is preferable to perform a stretching treatment on the carbon fiber precursor. By performing a stretching treatment on the carbon fiber precursor, the acrylamide copolymer contained in the carbon fiber precursor is oriented, and the tensile strength of the flame-retardant fiber tends to be improved. The stretching treatment is preferably carried out at least during heating at the flame-proofing treatment temperature. From the viewpoint of improving the tensile strength of the flame-resistant fiber, it is preferable to carry out a drawing treatment also during the temperature rise up to the flame-resistant treatment temperature. The stretching treatment may be carried out while controlling the moisture absorption rate during the spinning treatment or in a step prior to the flame retardant treatment.

[0088] During the stretching treatment, the tension applied to the carbon fiber precursor is preferably 0.03 mN / tex to 2000 mN / tex, more preferably 0.05 mN / tex to 500 mN / tex, even more preferably 0.07 mN / tex to 200 mN / tex, and particularly preferably 0.1 mN / tex to 100 mN / tex. In the present disclosure, the tension (unit: mN / tex) applied to the carbon fiber precursor is a value obtained by dividing the tension (unit: mN) applied to the carbon fiber precursor during the flame retardant treatment by the fineness (unit: tex) of the carbon fiber precursor in an absolute dry state, that is, the tension per unit fineness of the carbon fiber precursor. The tension can be adjusted by adjusting the speed at the inlet and outlet of a heating device such as a flame-proofing furnace, or by using a load cell, a spring, a weight, an air cylinder, or the like.

[0089] The flame retardant treatment time (heating time at the flame retardant treatment temperature) is not particularly limited, but from the viewpoint of carbonization yield and production costs, it is preferably 1 minute to 180 minutes, more preferably 2 minutes to 120 minutes, even more preferably 3 minutes to 60 minutes, particularly preferably 4 minutes to 50 minutes, and most preferably 5 minutes to 40 minutes. The flame-proofing treatment time may be set to a long time of more than 3 hours.

[0090] The density of the flame-retardant fiber is not particularly limited, but from the viewpoints of carbonization yield, productivity, etc., it is preferably 1.30 g / cm 3 ~1.75g / cm 3 and preferably 1.35 g / cm 3 ~1.70g / cm 3 More preferably, it is 1.37 g / cm 3 ~1.65g / cm 3 More preferably, it is 1.39 g / cm 3 ~1.60g / cm 3 It is particularly preferable that the density is 1.44 g / cm 3 ~1.55g / cm 3 It is most preferable that:

[0091] The average fiber diameter of the flame-resistant fiber is not particularly limited, but from the viewpoint of the tensile strength of the obtained carbon fiber, it is preferably 3 nm to 300 μm, more preferably 30 nm to 150 μm, even more preferably 1 μm to 60 μm, particularly preferably 2 μm to 30 μm, and most preferably 3 μm to 20 μm, and may be 5 μm to 15 μm.

[0092] From the viewpoint of carbonization yield, the average fiber diameter of the flame-resistant fiber is preferably at least 5% smaller than the average fiber diameter of the carbon fiber precursor, more preferably at least 10% smaller, even more preferably at least 15% smaller, particularly preferably at least 20% smaller, most preferably at least 25% smaller, and may be at least 30% smaller.

[0093] Carbonized fibers can be produced by subjecting the flame-retardant fibers to a carbonization treatment. The carbonization treatment refers to a treatment for carbonizing a carbon fiber precursor, and means performing a heat treatment in a low-oxygen environment (preferably an environment in which oxygen is blocked).

[0094] The carbonization method may be a method in which the flame-retardant fiber is subjected to a heat treatment in an inert gas (nitrogen, argon, helium, etc.) atmosphere at a temperature higher than that in the flame-retardant treatment. The above-mentioned carbonization treatment carbonizes the flame-retardant fiber to obtain carbon fiber. The heating temperature in the carbonization treatment is preferably 500°C or higher, more preferably 1000°C or higher, even more preferably 1100°C or higher, particularly preferably 1200°C or higher, and most preferably 1300°C or higher. The upper limit of the heating temperature is preferably 3000° C. or lower, and more preferably 2500° C. or lower. The heating time in the carbonization treatment is not particularly limited, but is preferably from 30 seconds to 60 minutes, and more preferably from 1 minute to 30 minutes. In the present disclosure, the "carbonization treatment" may also include "graphitization" which is generally performed by heating at a temperature of 2000°C to 3000°C in an inert gas atmosphere. The carbonization process may include multiple heat treatments. For example, a heat treatment (preliminary carbonization treatment) can be first performed at a temperature less than 1000°C, then a heat treatment (carbonization treatment) can be performed at a temperature of 1000°C or higher, and finally a heat treatment (graphitization treatment) can be performed at a temperature of 2000°C or higher.

[0095] The average fiber diameter of the carbon fibers is not particularly limited, but from the viewpoint of tensile strength, it is preferably 3 nm to 300 μm, more preferably 30 nm to 150 μm, even more preferably 1 μm to 60 μm, even more preferably 2 μm to 20 μm, particularly preferably 3 μm to 15 μm, and most preferably 5 μm to 10 μm. EXAMPLES

[0096] The above embodiment will be specifically described below with reference to examples, but the above embodiment is not limited to these examples.

[0097] [Example 1] Phosphoric acid was dissolved in water so that the amount of phosphoric acid was 3 parts by mass per 100 parts by mass of an acrylamide copolymer (acrylamide (AM) / acrylonitrile (AN) / acrylic acid (AA)=60 / 35 / 5 (molar ratio)). Next, adipic dihydrazide and 2-ethyl-4-methylimidazole were dissolved. Furthermore, the acrylamide copolymer was added to this aqueous solution and heated to 70° C. to dissolve the acrylamide copolymer, thereby obtaining an aqueous solution of the acrylamide copolymer with an acrylamide copolymer concentration of 50% by mass.

[0098] [Examples 2 to 6, Comparative Examples 1 to 5] An aqueous solution of an acrylamide copolymer was obtained in the same manner as in Example 1, except that the conditions for the polyfunctional amino group-containing compound, the nitrogen-containing heterocyclic compound, and the phosphoric acid were changed to those shown in Table 1. The unit of the content of each component shown in Table 1 is "parts by mass."

[0099] The aqueous solution of the resulting acrylamide copolymer was used to measure its initial viscosity and its viscosity after storage for 24 hours, 48 ​​hours, and 72 hours. In addition, a carbon fiber precursor was prepared using the obtained aqueous solution of the acrylamide copolymer, and the tensile strength was measured. Furthermore, a carbon fiber precursor was prepared using the obtained aqueous solution of the acrylamide copolymer, and then the precursor was subjected to a flame retardant treatment and its shape retention was evaluated. The measurement and evaluation methods are as follows.

[0100] <Initial viscosity> The viscosity (viscosity A) of the obtained aqueous solution of the acrylamide copolymer was measured at 70°C using a viscometer TVC-10 (B-type viscometer) manufactured by Toyo Sangyo while being heated with a hot stirrer. A No. 5 rotor was used for the measurement, and the rotation speed was set to 10 rpm. The viscosity at the point when it was visually confirmed that the acrylamide copolymer was uniformly dissolved was taken as the initial viscosity. The measurement results are shown in Table 1.

[0101] <Viscosity after storage for 24 hours, 48 ​​hours, and 72 hours> The aqueous solution of the acrylamide copolymer was stored in a screw test tube, and the screw test tube was immersed in a water tank maintained at 70°C. The viscosity measured 24 hours after it was visually confirmed that the acrylamide copolymer was uniformly dissolved was taken as the viscosity after 24 hours of storage (viscosity B). The same was true for the viscosities after 48 and 72 hours of storage. Each viscosity was measured in the same manner as for the initial viscosity. The measurement results are shown in Table 1. In Comparative Example 1 and Comparative Example 2, the viscosity after 24 hours of storage could not be measured because the gelation occurred after 24 hours of storage. Therefore, the viscosity after 48 hours and 72 hours of storage was not measured in Comparative Example 1 and Comparative Example 2. Both are indicated as "-" in Table 1.

[0102] <Tensile strength> A carbon fiber precursor bundle (800 fibers, single fiber diameter: 20 μm) was produced by dry spinning using an aqueous solution of an acrylamide copolymer. A single fiber was taken out from the fiber bundle of the carbon fiber precursor, and a tensile test (gauge length: 25 mm, tensile speed: 1 mm / min) was performed at room temperature (25 ° C.) in accordance with JIS R7606 using a micro strength evaluation tester (product name "Micro Autograph MST-I", manufactured by Shimadzu Corporation) to measure the tensile strength. The average value of five measurements was used as the tensile strength. The fiber diameters of eight random locations on the precursor fiber bundle were measured using a digital microscope VHX-1000 manufactured by Keyence Corporation, and the average value between the thinnest and thickest locations was used as the test piece diameter to calculate the tensile strength. The measurement results are shown in Table 1. In Examples 2 to 4 and Comparative Example 5, no measurement was performed. In Comparative Example 1 and Comparative Example 2, the tensile strength could not be measured because no carbon fiber precursor was obtained.

[0103] <Shape retention> A carbon fiber precursor bundle (800 fibers, single fiber diameter: 20 μm) was produced by dry spinning using an aqueous solution of an acrylamide copolymer. A fiber bundle of about 5 cm in length was cut out from 800 fiber bundles of the carbon fiber precursor. The fiber bundle was placed in a 100 mL glass beaker and flame-retarded by gradually increasing the temperature using a hot air circulation dryer at 150°C for 1 hour, 200°C for 1 hour, 250°C for 1 hour, and 300°C for 1 hour, to obtain a flame-retardant fiber. The appearance of the obtained flame-retardant fiber was visually observed, and the shape retention was evaluated. The evaluation criteria are as follows. A: No adhesion or aggregation is observed. B: Fusion or aggregation was observed. The evaluation results are shown in Table 1. In Comparative Examples 1 and 2, the shape retention could not be evaluated because no carbon fiber precursor was obtained. No evaluation was performed in Comparative Example 5. Both are indicated as "-" in Table 1.

[0104] [Table 1]

[0105] As shown in Table 1, in Examples 1 to 6, since the compositions contain an acrylamide copolymer containing 30 mol % or more of an acrylamide monomer unit and a vinyl monomer unit having a reactive group, a heterocyclic compound containing a nitrogen atom, and water, it was found that the increase in viscosity over time was suppressed and the compositions had excellent storage stability. On the other hand, in Comparative Examples 1 and 2, a heterocyclic compound containing a nitrogen atom was not included, and it was found that the initial viscosity was very high.In Comparative Examples 3 to 5, a heterocyclic compound containing a nitrogen atom was not included, and it was confirmed that the viscosity increased over time.

[0106] It was found that in Examples 1, 5 and 6, the tensile strength of the carbon fiber precursor was high compared to Comparative Examples 3 and 4. Moreover, it was found that in Examples 1 to 6, the flame-resistant fibers had excellent shape retention.

Claims

1. an acrylamide copolymer containing 30 mol % or more of an acrylamide monomer unit and a vinyl monomer unit having a reactive group; a heterocyclic compound containing a nitrogen atom; and water.

2. The composition of claim 1 further comprising a compound having a multifunctional amino group.

3. The composition according to claim 1 or 2, wherein the vinyl monomer unit having a reactive group is an unsaturated carboxylic acid unit.

4. The viscosity of a composition containing 50% by mass of an acrylamide-based copolymer is defined as viscosity A, and the viscosity of a composition containing 50% by mass of an acrylamide-based copolymer after storage at 70° C. for 24 hours is defined as viscosity B. The composition according to claim 1 or 2, wherein the viscosity B is within twice the viscosity A and is 100 Pa·s or less.

5. an acrylamide copolymer containing 30 mol % or more of an acrylamide monomer unit and a vinyl monomer unit having a reactive group; A carbon fiber precursor comprising:

6. The carbon fiber precursor according to claim 5 , further comprising a compound having a multifunctional amino group.

7. The carbon fiber precursor according to claim 5 or 6, wherein the vinyl-based monomer unit having a reactive group is an unsaturated carboxylic acid unit.

8. A method for producing a carbon fiber precursor, comprising: a step of spinning a composition containing an acrylamide-based copolymer containing 30 mol % or more of an acrylamide-based monomer unit and a vinyl-based monomer unit having a reactive group, a heterocyclic compound containing a nitrogen atom, and water.

9. The method for producing a carbon fiber precursor according to claim 8 , wherein the composition further contains a compound having a multifunctional amino group.

10. The method for producing a carbon fiber precursor according to claim 8 or 9, wherein the vinyl monomer unit having a reactive group is an unsaturated carboxylic acid unit.

Citation Information

Patent Citations

  • Carbon material precursor composition, method for producing same, and method for producing carbon material using same

    JP2019172800A